ESG Disclosure Component and Firm Performance in PROPER-Rated Indonesian Listed Firms: Evidence from ROA and Tobin’s Q - Patricia Diana; Rosita Suryaningsih; John CG Lee (Yayasan Ilomata, 2026)
Stakeholder demand for ESG disclosure has increased the need to examine whether sustainability-related information is associated with firm performance, particularly in emerging markets where prior findings remain mixed. Many previous studies treat ESG disclosure as an aggregate measure, leaving limited evidence on how environmental, social, and governance components are separately related to different performance outcomes. This study addresses this gap by examining component-level ESG disclosure among PROPER-rated Indonesian listed companies and comparing its association with accounting-based performance, measured by return on assets (ROA), and market-based performance, measured by Tobin’s Q. This study uses a quantitative approach with multiple linear regression/pooled OLS on data from Indonesian listed companies receiving PROPER ratings during 2021–2023. Using purposive sampling, the final sample consists of 26 companies and 78 firm-year observations. The results show that ESG disclosure components are associated differently with ROA and Tobin’s Q. For ROA, Environmental Score (E Score) and Social Score (S Score) are not statistically significant, while Governance Score (G Score) is positively significant. For Tobin’s Q, E Score, S Score, and G Score are statistically significant but E Score has negatively associated with Tobin’s Q. E Score shows a negative direction in both performance models, which may reflect additional compliance, reporting, monitoring, and environmental investment costs associated with environmental disclosure. In contrast, G Score is positively significant across both ROA and Tobin’s Q, indicating that governance disclosure is consistently associated with stronger firm performance. This study contributes to ESG literature by providing component-level evidence from PROPER-rated Indonesian listed firms and by distinguishing between accounting-based and market-based performance measures.